2014
DOI: 10.1016/j.stemcr.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Is Necessary for Proficient Telomere Elongation and Genomic Stability of Induced Pluripotent Stem Cells

Abstract: SummaryThe NAD-dependent deacetylase SIRT1 is involved in chromatin silencing and genome stability. Elevated SIRT1 levels in embryonic stem cells also suggest a role for SIRT1 in pluripotency. Murine SIRT1 attenuates telomere attrition in vivo and is recruited at telomeres in induced pluripotent stem cells (iPSCs). Because telomere elongation is an iPSC hallmark, we set out to study the role of SIRT1 in pluripotency in the setting of murine embryonic fibroblasts reprogramming into iPSCs. We find that SIRT1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
4
61
1
Order By: Relevance
“…Our results indicate that under conditions of oxidative stress induced by CSE, TPP1 was acetylated and possibly degraded. Previous studies have shown that Sirt1 interacts with telomeres and maintains telomere length (34,35). Hence, we surmise that CS-induced TPP1 acetylation and reduction are attributable to Sirt1 reduction.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Our results indicate that under conditions of oxidative stress induced by CSE, TPP1 was acetylated and possibly degraded. Previous studies have shown that Sirt1 interacts with telomeres and maintains telomere length (34,35). Hence, we surmise that CS-induced TPP1 acetylation and reduction are attributable to Sirt1 reduction.…”
Section: Discussionmentioning
confidence: 50%
“…Further study is ongoing to determine whether Sirt1 protects against CS-induced TPP1 acetylation and to identify the corresponding residues. In addition to TPP1, Sirt1 may regulate other molecules including telomerase, poly ADP ribose polymerase, and histones, thereby protecting against CS-induced telomere dysfunction (34,35); this needs further investigation. CS treatment exaggerated the alveolar damage and led to reduced TPP1 levels in the Sirt1 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we suggest that mTORC1 helps drive cell division of ISCs, while SIRT1 promotes the decision for self-renewal as opposed to differentiation. In this regard, it is interesting to note that embryonic stem cells and IPS cells express extremely high levels of SIRT1 (Calvanese et al, 2010;De Bonis et al, 2014;Saunders et al, 2010) and this might enhance the self-renewal ability of these pluripotent cells.…”
Section: Implications For Self-renewal Versus Differentiationmentioning
confidence: 99%
“…Conversely, it is unlikely that lack of TERT activation causes partial reprogramming as TERT expression and/or activity does not guarantee pluripotency. 28,35,47,48 However, telomere length is touted as a biomarker of reprogramming, with hiPSC telomere lengths plateauing close to the hESC telomere length of about 12 kbp despite continued high telomerase expression. 49 Such stabilization of telomere length, in addition to proper downregulation of hTERT following differentiation, is a strong hallmark of non-transformed human pluripotent stem cells.…”
Section: Telomeres and Pluripotent Stem Cellsmentioning
confidence: 99%
“…65,72,73 Indirect evidence of C-MYC's importance is provided by the knockdown of SIRT1 which represses C-MYC, and accompanies a reduction in mTERT levels. 47 However, C-MYC is not required for reprogramming and its expression level is generally not correlated with TERT levels post-reprogramming, raising the question of whether C-MYC actually plays a major role in maintaining TERT expression. 32,33,53 It is possible that this effect is still mediated through KLF4 as SIRT1 also affects NANOG expression, which, in turn can regulate KLF4 and C-MYC through feedback loops with other pluripotency factors (for example OCT3/4 and mir145).…”
Section: Pluripotency and Canonical Tert Functionsmentioning
confidence: 99%